Answer:
The solution of the given equations is (-3,2)
Step-by-step explanation:
Step:1
The Given equations are 2 x+3 y=0 .......(1)
x+2 y-1 =0.........(2)
Step 2:-
Solving both equations by using substitution method
multiply equation (2) with number '2' ,
2 x+4 y-2=0.......(3)
subtracting the equations (1) and (3) and cancelled 'x' terms
we get [tex]3y-4y=0-2[/tex]
[tex]y=2[/tex]
Step 3:-
substitute y= 2 in equation (1) we get
[tex]2 x+3 y=0[/tex]
[tex]2 x+3(2)=0[/tex]
[tex]2 x=-6[/tex]
[tex]x=-3[/tex]
Final answer:-
The solution of the given equations is (-3,2)